A botanist's guide to rituals and revenge [large type] - Khavari, Kate (Khavari, Kate. Saffron Everleigh mystery, 2025)
"Saffron Everleigh returns to Ellington Manor after her grandfather suffers a heart attack. Back in her childhood home for the first time in years, Saffron faces tense family relationships made worse by the presence of the enigmatic Bill Wyatt, hired on as a doctor to the ailing Lord Easting. But the man is no doctor-in reality, he is a mysterious figure involved in the trafficking of dangerous government secrets, and his presence at Ellington can only mean trouble. When their neighbors, the Hales, invite a spiritual medium into the village who starts angling for Saffron's mother's attention, Saffron realizes that there is more afoot in her hometown than she originally thought. Not to mention inviting Alexander to Ellington has put their budding relationship under her family's microscope. As tensions rise at Ellington, Bill demands that Saffron hand over old research documents belonging to her late father. With her relatives under his power as their "doctor," Saffron fears she may be forced to surrender the files along with her hopes of ever understanding her father's obscure legacy. Nothing and no one is as they seem at Ellington. It's through the perfumed haze of the séance's smoke that Saffron must search for the truth before it's too late."--